The critical role of dysregulated autophagy in the progression of diabetic kidney disease - Ziwei Zhang; Yuting Sun; Jiaojiao Xue; De Jin; Xiangyan Li; Daqing Zhao; Fengmei Lian; Wenxiu Qi; Xiaolin Tong (Frontiers Media S.A., 2022)
Diabetic kidney disease (DKD) is one of the major public health problems in society today. It is a renal complication caused by diabetes mellitus with predominantly microangiopathy and is a major cause of end-stage renal disease (ESRD). Autophagy is a metabolic pathway for the intracellular degradation of cytoplasmic products and damaged organelles and plays a vital role in maintaining homeostasis and function of the renal cells. The dysregulation of autophagy in the hyperglycaemic state of diabetes mellitus can lead to the progression of DKD, and the activation or restoration of autophagy through drugs is beneficial to the recovery of renal function. This review summarizes the physiological process of autophagy, illustrates the close link between DKD and autophagy, and discusses the effects of drugs on autophagy and the signaling pathways involved from the perspective of podocytes, renal tubular epithelial cells, and mesangial cells, in the hope that this will be useful for clinical treatment.